Literature Review of Socio-Cultural Studies on Incidence of Early Childhood Marriage - Haryanti, Maharani Nurul; Kusumaningtyas, Bethari Mukti; Umaroh, Ayu Khoirotul (Griya Widya: Journal of Sexual and Reproductive Health, 2024)
Background: Early childhood marriages that occur in Indonesia are caused by the existence of norms that apply in traditional societies, which are closely related to socio-economic relations between generations. Early marriage is still a serious problem faced in Indonesia. Method: This research method is a literature review, which is a research method that summarizes various research journals from the Google Scholar, PubMed, and Scopus databases. With inclusion criteria, namely research subjects adolescents before the age of 18 years, articles using quantitative methods with a cross-sectional survey design on publications with ISSN or indexed in SINTA or SCOPUS, articles using Indonesian and English, articles accessed in full text, and are publications from the last 5 years. Result: The results of this literature review research, obtained from ten journals related to socio-cultural factors that influence the occurrence of early marriage in adolescents. Of the ten journals, there are four variables from social factors, namely: economics, knowledge, the role of parents, promiscuity, and one variable from cultural factors, namely customs or traditions. Of the several variables that most influence early marriage, namely, social factors of knowledge and cultural factors. Implication: The implications of this study are researcher can further expand the variables of social factors related to early childhood marriage, and cultural factors can be explored in more detail that explain the culture related to early marriage using quantitative and qualitative methods. Novelty: This literature review aims to determine the socio-cultural factors that influence the occurrence of early marriage in adolescents.